2019
DOI: 10.1097/ajp.0000000000000721
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of Skin Conductance For Assessing Acute Pain in Infants

Abstract: Objectives: Measuring pain in infants is important but challenging, as there is no “gold standard.” The measurement of skin conductance (SC) is considered to be a measure of stress and as a surrogate indicator of pain. The objectives of this study were to identify the extent of research conducted and to synthesize the validity evidence of SC for assessing acute pain in infants. Methods: The Arksey and O’Malley framework for scoping reviews was followed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…Secondary outcomes in the RCT are: a) changes in galvanic skin response (GSR) (area small peaks, area huge peaks, peaks per second, average rise time, average peak), which is obtained via three electrodes on the infant's foot [52], b) parents' rating of the infant's pain, c) parents' rating of their own stress during the procedure and d) parents' rating of how beneficial the pain management they were involved in felt to them and their infant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondary outcomes in the RCT are: a) changes in galvanic skin response (GSR) (area small peaks, area huge peaks, peaks per second, average rise time, average peak), which is obtained via three electrodes on the infant's foot [52], b) parents' rating of the infant's pain, c) parents' rating of their own stress during the procedure and d) parents' rating of how beneficial the pain management they were involved in felt to them and their infant.…”
Section: Discussionmentioning
confidence: 99%
“…As an indicator of pain, skin conductance measurements have detected increased sweating in newborn infants < 28 + 0 postnatal age submitted to heel lancing [53]. GSR have been tested in several neonatal pain studies on term and preterm infants, measuring skin conductance that reflects pain-related activation of the sympathetic nervous system [52][53][54][55]. Analyses of GSR are presented with the following variables; area small peaks, area huge peaks (both representing forcefulness of sympathetic nerve firing), peaks per second (the rate of firing in the sympathetic nerves), average rise time, average peak.…”
Section: Study Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the scores of SC can be easily and quickly understood by clinicians and researchers. The number of SC waves per second (NWps) was recommended by many previous studies and the user manual of SC device for pain assessment (Hu et al, 2019;Med-Storm Innovation AS, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A recent scoping review, which included 28 studies with 1,061 infants, synthesized the validity of SC for assessing acute pain in hospitalized infants (Hu et al, 2019). The results showed that SC might be a promising pain assessment method in infants.…”
Section: Introductionmentioning
confidence: 99%